The relationship between occupational sun exposure and non-melanoma skin cancer: clinical basics, epidemiology, occupational disease evaluation, and prevention - Fartasch, Manigé; Diepgen, Thomas L. (Deutsches Ärzteblatt, 2012)
BACKGROUND: The cumulative effect of solar ultraviolet (UV) radiation is responsible for the worldwide increase in non-melanoma skin cancer, a category that includes squamous cell carcinoma and its precursors (the actinic keratoses) as well as basal-cell carcinoma. Non-melanoma skin cancer is the most common type of cancer in areas of the world with a light-skinned population. The occupational exposure to UV radiation is high in many outdoor occupations; recent studies suggest that persons working in such occupations are more likely to develop non-melanoma skin cancer. METHODS: On the basis of a selective review of the literature, we present the current state of knowledge about occupational and non-occupational UV exposure and the findings of meta-analyses on the association of outdoor activity with non-melanoma skin cancer. We also give an overview of the current recommendations for prevention and for medicolegal assessment. RESULTS: Recent meta-analyses have consistently documented a significantly higher risk of squamous cell carcinoma of the skin among persons who work outdoors (odds ratio [OR] 1.77, 95% confidence interval [CI] 1.40-2.22, p<0.001). There is also evidence for an elevated risk of basal-cell carcinoma (OR 1.43, 95% CI 1.23-1.66, p = 0.0001), but the effect is of lesser magnitude and the study findings are not as uniform. CONCLUSION: The association of occupational exposure to solar UV radiation with squamous cell carcinoma, including actinic keratosis, has been conclusively demonstrated. It follows that, in Germany, suspected non-melanoma skin cancer in persons with high occupational exposure to UV radiation should be reported as an occupational disease under § 9, paragraph 2 of the Seventh Book of the German Social Code (Sozialgesetzbuch, SGB VII). Preventive measures are urgently needed for persons with high occupational exposure to UV radiation.
Gesehen am 29.10.2018